Positive electrode electrolyte of flow battery, flow battery containing positive electrode electrolyte and preparation method of flow battery
By adding components such as sodium polyacrylate to the positive electrode electrolyte of the liquid flow battery, the problem of precipitation of the electrolyte at low temperatures is solved, and the low-temperature performance and scope of application of the battery are improved.
Patent Information
- Application Number
- CN202411548598.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-18
AI Technical Summary
The positive electrode electrolyte of the flow battery has a precipitation problem at low temperatures, which affects its performance.
A positive electrode electrolyte containing ferrocyanide, stabilizer, alkaline components, auxiliary electrolytes, additives (sodium polyacrylate) and water is used to improve the low-temperature performance of the electrolyte by adjusting the component ratio and adding sodium polyacrylate.
It effectively improves the low-temperature performance of the positive electrode electrolyte of the flow battery, expands its use scenarios and application scope, and ensures the stability and performance of the battery under low temperature conditions.
Smart Images

Figure CN119650779A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage technology, and in particular to a positive electrode electrolyte of a liquid flow battery, a liquid flow battery containing the positive electrode electrolyte, and a preparation method thereof. Background Art
[0002] Liquid flow battery is a new type of electrochemical energy storage technology. It was first proposed in 1974. It is a high-performance battery that uses separated positive and negative electrolytes and circulates separately. It has the characteristics of high capacity, wide application scenarios, and long cycle life. The principle of liquid flow battery is to use the reversible redox reaction of positive and negative electrolytes to realize the mutual conversion of electrical energy and chemical energy. The characteristic of this battery is that its electrolyte is flowing, so it is called a "liquid flow" battery. In a liquid flow battery, the electrolyte flows in a cycle over and over again to achieve the storage and release of electrical energy.
[0003] The electrodes, ion-conducting membranes and electrolytes of flow batteries are its basic components. The electrodes are mainly responsible for the electrochemical reaction, providing a reaction site, and do not participate in the reaction themselves. When charging, 100% SOC can be achieved, and the battery power can be regulated by adjusting the number of battery stacks or adjusting the electrode area. The active material is dissolved in the electrolyte and stored in the tank. The battery capacity can be regulated by adjusting the electrolyte parameters and the tank capacity.
[0004] In the prior art, the positive electrode electrolyte has a precipitation problem under low temperature conditions, which affects the low temperature performance of the liquid flow battery. Therefore, the positive electrode electrolyte needs to be treated accordingly to improve the low temperature performance of the positive electrode electrolyte, thereby ensuring that the performance of the liquid flow battery is not affected by low temperature. Summary of the invention
[0005] The present application mainly provides a positive electrode electrolyte of a liquid flow battery, a liquid flow battery containing the positive electrode electrolyte, and a preparation method thereof, so as to solve the problem that the performance of the positive electrode electrolyte of the liquid flow battery deteriorates at low temperatures.
[0006] In order to solve the above technical problems, a technical solution adopted in the present application is: to provide a positive electrode electrolyte for a liquid flow battery, the positive electrode electrolyte comprising: ferrocyanide, a stabilizer, an alkaline component, an auxiliary electrolyte, an additive and water, wherein:
[0007] The total iron concentration is 0.1-2.0 mol / L, the molar ratio of the stabilizer to Fe is 0.05-1.0, the alkaline component is 0.5-3.0 mol / L, the auxiliary electrolyte is 0-1.0 mol / L, and the additive is sodium polyacrylate.
[0008] In a possible implementation, the sodium polyacrylate accounts for 0.8 to 1.2‰.
[0009] In a possible implementation, the sodium polyacrylate is used to improve the low-temperature performance of the positive electrode electrolyte.
[0010] In a possible implementation, the ferrocyanide is one or more of sodium ferrocyanide, potassium ferrocyanide, and lithium ferrohydride.
[0011] In a possible embodiment, the stabilizer is one or more of citric acid, hydroxyethylidene diphosphonic acid, sodium ethylenediamine di-o-phenylacetate, aminotrimethylenephosphonic acid, sodium ethylenediamine tetra-methylene phosphate, and sulfosalicylic acid.
[0012] In a possible implementation, the alkaline component includes one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide.
[0013] In a possible implementation, the auxiliary electrolyte includes one or more of potassium chloride, sodium chloride, and lithium chloride.
[0014] Another technical solution adopted in the present application is to propose a liquid flow battery, comprising the positive electrode electrolyte as described above.
[0015] Another technical solution adopted by the present application is: a method for preparing a positive electrode electrolyte is proposed, which is used for the positive electrode electrolyte as described above, comprising:
[0016] S10: adding sodium polyacrylate into pure water and stirring evenly to prepare an additive mother solution;
[0017] S20: adding the additive mother solution to the positive electrode electrolyte base solution as required, wherein the proportion of the sodium polyacrylate in the formed solution is 0.8 to 1.2‰.
[0018] In a possible implementation, the step of adding sodium polyacrylate to pure water and stirring evenly to prepare an additive mother solution comprises:
[0019] S11: Mix 1.25 g of sodium polyacrylate with 100 mL of pure water and stir well.
[0020] The beneficial effect of the present application is: different from the prior art, the present application discloses a positive electrode electrolyte for a liquid flow battery, which improves the low-temperature performance of the positive electrode electrolyte of the liquid flow battery by adding additives to the positive electrode electrolyte, expands the use scenarios of the positive electrode electrolyte of the liquid flow battery, and broadens the scope of application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work, among which:
[0022] Figure 1 This is a test result diagram of the effect of 1‰ PAAS additive on the electrochemical performance of the positive electrode electrolyte in one embodiment of the present application;
[0023] Figure 2 This is a test result diagram of the effect of 1‰ lignin additive on the electrochemical performance of the positive electrode electrolyte in one embodiment of the present application;
[0024] Figure 3 This is a test result diagram of the effect of a 1‰ PAAS additive placed at 60°C for 1 day on the electrochemical performance of an oxidized positive electrode electrolyte in an embodiment of the present application;
[0025] Figure 4 This is a test result diagram of the effect of a 1‰ PAAS additive placed at 60°C for 4 days on the electrochemical performance of an oxidized positive electrode electrolyte in an embodiment of the present application;
[0026] Figure 5 This is a test result diagram of the effect of a 1‰ PAAS additive placed at 60°C for 7 days on the electrochemical performance of an oxidized positive electrode electrolyte in an embodiment of the present application;
[0027] Figure 6 This is a test result diagram of the effect of a 1‰ PAAS additive on the electrochemical performance of an oxidized positive electrode electrolyte placed at 60°C for 12 days in an embodiment of the present application. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0029] The terms "first", "second", "third" in the embodiments of the present application are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second", "third" can expressly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.
[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0031] The present application embodiment provides a positive electrode electrolyte for a liquid flow battery, the positive electrode electrolyte comprising: ferrocyanide, a stabilizer, an alkaline component, an auxiliary electrolyte, an additive and water, wherein:
[0032] The total iron concentration is 0.1-2.0 mol / L, the molar ratio of the stabilizer to Fe is 0.05-1.0, the alkaline component is 0.5-3.0 mol / L, the auxiliary electrolyte is 0-1.0 mol / L, and the additive is sodium polyacrylate.
[0033] The positive electrode electrolyte in this embodiment is suitable for liquid flow batteries, specifically alkaline all-iron liquid flow batteries, which are liquid-phase electrochemical energy storage devices whose active substances are completely dissolved in the electrolyte. The liquid flow battery in this embodiment, its positive electrode electrolyte may include ferrocyanide, stabilizer, alkaline component, auxiliary electrolyte, additive and water, and the negative electrode electrolyte may include organic complexing agent, promoting component, alkaline component, auxiliary electrolyte.
[0034] In one embodiment, the proportion of sodium polyacrylate is 0.8-1.2‰, and 1‰ is selected in this embodiment, which can improve the low-temperature performance of the positive electrode electrolyte without affecting the electrical properties of the positive electrode electrolyte.
[0035] In one embodiment, sodium polyacrylate is used to improve the low temperature performance of the positive electrode electrolyte. Specifically, the low temperature performance may include precipitation of the positive electrode electrolyte at low temperature. This embodiment effectively improves the low temperature precipitation of the positive electrode electrolyte by adding sodium polyacrylate as an additive, thereby improving the versatility and reliability of the positive electrode electrolyte.
[0036] In one embodiment, the ferrocyanide is one or more of sodium ferrocyanide, potassium ferrocyanide, and lithium ferrohydride.
[0037] In one embodiment, the stabilizer is one or more of citric acid, hydroxyethylidene diphosphonic acid, sodium ethylenediamine di-o-phenylacetate, aminotrimethylenephosphonic acid, sodium ethylenediamine tetra-methylenephosphate, and sulfosalicylic acid.
[0038] In one embodiment, the alkaline component includes one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide.
[0039] In one embodiment, the auxiliary electrolyte includes one or more of potassium chloride, sodium chloride, and lithium chloride.
[0040] Another embodiment of the present application provides a liquid flow battery, comprising the positive electrode electrolyte as described above. The liquid flow battery using the positive electrode electrolyte containing sodium polyacrylate as an additive has better low temperature performance, better usage scenarios and application scope.
[0041] Another embodiment of the present application provides a method for preparing a positive electrode electrolyte, which is used for the positive electrode electrolyte as described above, comprising:
[0042] S10: adding sodium polyacrylate into pure water and stirring evenly to prepare an additive mother solution;
[0043] S20: Add the additive mother solution to the positive electrode electrolyte base solution as required, and the proportion of sodium polyacrylate in the formed solution is 0.8 to 1.2‰.
[0044] In one embodiment, the step of adding sodium polyacrylate to pure water and stirring evenly to prepare an additive mother solution comprises:
[0045] S11: Mix 1.25 g of sodium polyacrylate with 100 mL of pure water and stir well.
[0046] Then, 2 mL of the obtained additive mother solution was added to 25 mL of a positive electrode electrolyte base solution having a concentration of 1 M to obtain a positive electrode electrolyte having good low temperature performance.
[0047] The present application is further explained below by way of examples.
[0048] CMC (sodium carboxymethyl cellulose), lignin, PAAS (sodium polyacrylate) were selected as the additives to be tested, as well as 1M positive electrode electrolyte.
[0049] Prepare additive masterbatch, including:
[0050] 1.25g CMC was mixed evenly with 50mL pure water to prepare 25mg / mL CMC stock solution;
[0051] 1g lignin was mixed evenly with 50mL pure water to prepare 20mg / mL lignin mother solution;
[0052] 1.25 g PAAS was mixed with 100 mL pure water to prepare a 12.5 mg / mL PAAS stock solution;
[0053] Take 4 more containers (such as glass bottles) to prepare the test objects used in the experiment, including:
[0054] No. 1 is the control group, which is a 1M positive electrolyte without additives;
[0055] No. 2 to No. 4 are experimental groups, No. 2 is 2mL CMC mother solution + 50mL 1M positive electrolyte, No. 3 is 2mL lignin mother solution + 40mL 1M positive electrolyte, and No. 4 is 2mL PASS mother solution + 25mL 1M positive electrolyte. The masses of No. 2 to No. 4 are different, and the purpose is to mix the same proportion of components.
[0056] Put bottles 1 to 4 into the low-temperature circulation pump at the same time. Based on the fact that the 1M positive electrolyte without additives usually begins to precipitate at 7-8°C, the first set of preset temperatures is set to 8°C, 6.5°C and 3.5°C. After stabilizing at each temperature for a period of time, observe the precipitation of the liquid in the bottle to ensure possible precipitation, so as to derive the effect of each additive on the low-temperature performance of the positive electrolyte. Specifically, place the experimental group and the control group in a low-temperature circulation pump, and set the first set of preset temperatures. Each solution is first reduced to 8°C and left to stand for a period of time. After sufficient reaction and precipitation, observe and record the precipitation. Then cool the experimental group and the control group to 6.5°C, observe and record after standing for a period of time, and finally continue to cool to 3.5°C, observe and record after standing, and complete this low-temperature treatment. Standing after each cooling is to ensure that the solution is in a stable state to ensure the accuracy of the observed phenomena and results.
[0057] The results showed that the control group No. 1 bottle began to precipitate at 7-8°C, No. 2 bottle began to precipitate at below 6.5°C, and No. 3 and No. 4 bottles began to precipitate at below 3.5°C. Therefore, it is preliminarily believed that lignin and PAAS have a good effect in reducing the precipitation temperature.
[0058] Based on the above results, further electrochemical performance tests were carried out to continue analyzing the cathode electrolyte added with lignin and PAAS.
[0059] Take 15mL of positive electrolyte containing 1‰ lignin, 15mL of 1M positive electrolyte containing 1‰ PAAS, and add 21mL of 0.65M negative electrolyte to perform battery testing. Battery test results refer to Figure 1 and Figure 2 , Figure 1 The electrochemical performance test results of the positive electrode electrolyte containing 1‰ PAAS additive are shown in Figure 2. Figure 2 The electrochemical performance test results of the positive electrolyte containing 1‰ lignin additive are shown in Figure 2. Figure 1 and Figure 2 The horizontal axis is the number of times the battery is charged and discharged. The curves in the figure are charge and discharge efficiency, capacity retention rate, and energy efficiency from top to bottom.
[0060] The battery test is to place the electrolyte in a battery for actual use, and then perform a performance test on the battery to determine whether the additive has an effect on the performance of the positive electrode electrolyte. Specifically, the solution to be tested can be placed in a flow battery, and the flow battery can be charged and discharged to obtain the charge and discharge efficiency, capacity retention rate, and energy efficiency changes of the battery during multiple charge and discharge cycles, and to determine the effect of the additive on the electrochemical properties of the positive electrode electrolyte. In this embodiment, the number of charge and discharge cycles is not less than 250 times.
[0061] The results show that PAAS has little effect on battery performance, while lignin may reduce battery performance.
[0062] Based on the above results, the effect of PAAS on the positive electrolyte at high temperature was further tested, that is, by simulating the working environment of the positive electrolyte after a period of actual use, in order to test whether the additive has high-temperature hydrolysis, thereby adversely affecting the performance of the positive electrolyte. Considering the actual working conditions and environment, 200mL of 1M oxidized positive electrolyte was prepared, and 16.6g of 12.5mg / mL PAAS sol was added. After mixing evenly, it was placed in a 60°C oven. Parts were taken out for battery testing at 1 day, 4 days, 7 days and 12 days respectively. The test results refer to Figures 3 to 6 . Figures 3 to 6 The electrochemical performance test results of the battery after PAAS treatment at 60°C for 1 day, 4 days, 7 days, and 12 days, respectively. The horizontal axis in the figure is the number of battery charge and discharge times. Figure 3 and Figure 6 The middle curve from top to bottom is the charge and discharge efficiency, energy efficiency and capacity retention rate. Figure 4 and Figure 5 The middle curve from top to bottom is the charge and discharge efficiency, capacity retention rate and energy efficiency.
[0063] The results show that PAAS does not hydrolyze at 60°C and the battery performs normally within 100 charge and discharge cycles. However, over time, the battery's capacity decays significantly after 150-250 cycles.
[0064] At the same time, the oxidized cathode electrolyte was observed after being placed at 60°C. As time went by, red flocculent precipitates appeared at the bottom. Further preparation of the control group revealed that the oxidized cathode electrolyte was hydrolyzed by itself, eliminating the influence of PAAS.
[0065] Then, physical and chemical tests were performed on the experimental group and the control group to analyze the effect of PAAS on the physical and chemical properties of the positive electrode electrolyte. The results are shown in the following table:
[0066] density pH Viscosity (mPa·S) 1M positive electrolyte 1.24 13.8 1.76 1‰+1M positive electrolyte 1.23 13.78 3.20
[0067] It can be seen that the viscosity of the positive electrolyte increases slightly after adding PAAS, but it does not affect the fluidity of the positive electrolyte, and has little effect on the density and pH. Based on the above experiments, it can be considered that among CMC, lignin and PAAS, PAAS is the relatively best additive. Adding 1‰ PAAS can effectively reduce the precipitation temperature of the positive electrolyte and basically does not change the appearance color of the positive electrolyte. At the same time, it will not decompose itself at 60°C to affect the electrochemical properties of the positive electrolyte, and has no obvious effect on the physical and chemical properties of the positive electrolyte.
[0068] The above descriptions are merely embodiments of the present application and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A positive electrolyte for a liquid flow battery, characterized in that: The positive electrode electrolyte comprises: ferrocyanide, a stabilizer, an alkaline component, an auxiliary electrolyte, an additive and water, wherein: The total iron concentration is 0.1-2.0 mol / L, the molar ratio of the stabilizer to Fe is 0.05-1.0, the alkaline component is 0.5-3.0 mol / L, the auxiliary electrolyte is 0-1.0 mol / L, and the additive is sodium polyacrylate.
2. The positive electrolyte of the liquid flow battery according to claim 1, characterized in that: The sodium polyacrylate accounts for 0.8 to 1.2‰.
3. The positive electrode electrolyte of the liquid flow battery according to claim 1, characterized in that: The sodium polyacrylate is used to improve the low temperature performance of the positive electrode electrolyte.
4. The positive electrolyte of the liquid flow battery according to claim 1, characterized in that: The ferrocyanide is one or more of sodium ferrocyanide, potassium ferrocyanide and lithium ferrohydride.
5. The positive electrode electrolyte of the liquid flow battery according to claim 1, characterized in that: The stabilizer is one or more of citric acid, hydroxyethylidene diphosphonic acid, sodium ethylenediamine di-o-phenylacetate, aminotrimethylenephosphonic acid, sodium ethylenediamine tetra-methylene phosphate, and sulfosalicylic acid.
6. The positive electrode electrolyte of the liquid flow battery according to claim 1, characterized in that: The alkaline component includes one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.
7. The positive electrolyte of the liquid flow battery according to claim 1, characterized in that: The auxiliary electrolyte includes one or more of potassium chloride, sodium chloride and lithium chloride.
8. A liquid flow battery, characterized in that: Comprising the positive electrode electrolyte as described in any one of claims 1 to 7.
9. A method for preparing a positive electrode electrolyte, for use in the positive electrode electrolyte according to any one of claims 1 to 7, characterized in that: include: S10: adding sodium polyacrylate into pure water and stirring evenly to prepare an additive mother solution; S20: adding the additive mother solution to the positive electrode electrolyte base solution as required, wherein the proportion of the sodium polyacrylate in the formed solution is 0.8 to 1.2‰.
10. The method for preparing the positive electrode electrolyte according to claim 9, characterized in that: The step of adding sodium polyacrylate into pure water and stirring evenly to prepare an additive mother solution comprises: S11: Mix 1.25 g of sodium polyacrylate with 100 mL of pure water and stir well.